P.101 Response to high dose nocturnal diazepam in children with ESES. (November 2021) - Kiani, H; Go, C; Jones, KC; Connolly, MB; Smith, M; RamachandranNair, R
Abstract : Background: To assess the response to high dose daily nocturnal diazepam (HDD) in children with encephalopathy associated with electrical status epilepticus in sleep (ESES). Methods: A prospective cohort of patients (4-12 years), newly diagnosed with ESES, initiated on the first course HDD, was followed for ≤ 1-year. Sleep EEG scores (SES) pre and post HDD were evaluated. An EEG grading system based on both sleep spike wave index (sSWI) (Grade: 1-4) and distribution of epileptiform discharges (Grade: 0-4) was used and summed to yield an aggregate SES (ASES) (Grade: 1-8). Results: Eighteen eligible children (M:F 12:6; median age, 7.6 years) were initiated on first course HDD (median, 0.5 mg/kg/d). sSWI decreased from 85.7% (mean, SD 13.9) to 32.6% (mean, SD 37.1) at subsequent EEG (95% CI = -70.60- -35.62; p < 0.001). ASES decreased from 6.5 (SD 1.3) to 3.1 (SD 1.9) (95% CI = -4.17- -2.60; p < 0.001). EEG relapse after a period of improvement occurred in 10 children. Minimal response to HDD occurred in 2 children. Five patients manifested mild side effects; behavior (2), hyperactivity (2), and lethargy (1). Conclusions: HDD safely and significantly reduces both SWI and aggregate sleep EEG score in children with ESES.